Ophthalmomyiasis is not only a problem for rural regions of Eastern Anatolia of Turkey - Kuk, Salih; Yildirim, Suleyman; Ozden, Mehmet; Erensoy, Ahmet; Saki, Cem Ecmel (Int Scientific Literature, Inc, 2009)
Background: Ophthalmomyiasis externa results from infestation of the conjunctiva by the larval or maggot from of Oestrus ovis. It is common in sheep-farming areas, especially in Mediterranean countries. Case Report: A 40-year-old man was admitted to the ophthalmology outpatient clinic at State Hospital. He complained of a foreign-body sensation. He was living in a city center in Eastern Anatolia of Turkey. The larvae were removed and antibiotic drops and ointment were given to the patient. The larvae were first-instar Oestrus ovis larvae. Conclusions: The authors consider ophthalmomyiasis to be not only a problem of rural areas and subsequent examination is very important to ensure that no complications have occurred. It is hoped that this case encourages physicians to be aware of the diagnosis of ophthalmomyiasis externa and its complication and treatment.
Keywords: ophthalmomyiasis externa; Oestrus ovis; Turkey